Exploration and Practice of the Pre-Operational Urban Organic Renewal 3.0 Model: A Case Study of Baotou Hongjie Renewal and Renovation - XIA YILAN; ALBATTAT AHMAD; LI XINJIAN; LI YANG (International Journal of Multidisciplinary Research and Studies, 2024)
China's urban development has entered a stage of stock renewal, transitioning from extensive outward expansion to intensive intrinsic development in line with the overarching goals of "high-quality development" and "new quality productivity." This paper uses the redevelopment of the historical and cultural district of Baotou Red Street as a case study. From the perspective of pre-operational planning, it examines the current issues faced in China's urban organic renewal. The study explores market-oriented strategies and innovative practice models for urban organic renewal from various dimensions, including spatial characteristics, renewal ideas, business pattern creation, and operational strategies.